2012
DOI: 10.1111/j.1462-2920.2012.02792.x
|View full text |Cite
|
Sign up to set email alerts
|

Protoanemonin: a natural quorum sensing inhibitor that selectively activates iron starvation response

Abstract: Many Gram-negative bacteria employ cell-to-cell communication mediated by N-acyl homoserine lactones (quorum sensing) to control expression of a wide range of genes including, but not limited to, genes encoding virulence factors. Outside the laboratory, the bacteria live in complex communities where signals may be perceived across species. We here present a newly found natural quorum sensing inhibitor, produced by the pseudomonads Pseudomonas sp. B13 and Pseudomonas reinekei MT1 as a blind end in the biodegrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…and the honaucins from coral-associated cyanobacteria (Fig. 3E) [30,31]. Crude garlic extracts containing an inhibitor(s) of AHL-dependent QS were subjected to a clinical trial in P. aeruginosa-infected cystic fibrosis patients and although the results were not statistically significant (the patient numbers were too small), a trend towards improvement after oral garlic extract administration was noted [32].…”
Section: Inhibitors Of Ahl-based Qs Systems With Unknown Targetmentioning
confidence: 99%
“…and the honaucins from coral-associated cyanobacteria (Fig. 3E) [30,31]. Crude garlic extracts containing an inhibitor(s) of AHL-dependent QS were subjected to a clinical trial in P. aeruginosa-infected cystic fibrosis patients and although the results were not statistically significant (the patient numbers were too small), a trend towards improvement after oral garlic extract administration was noted [32].…”
Section: Inhibitors Of Ahl-based Qs Systems With Unknown Targetmentioning
confidence: 99%
“…Moreover, they found genes activation and gene products involved in the iron deficiency reaction. Thus, the quorum sensing inhibition, as a product of antibiotics, probably is a phenomenon found in bacterial groups' complex [14].…”
Section: Fig 3 Chelidonic Acidmentioning
confidence: 99%
“…It has antimicrobial and fungistatic, antimutagenic [12,13], sedative effect, it is active against gram-positive and acid-resistant bacteria, also it tones up the nervous system, activates the reticuloendothelial system and improves endopoez. Scientists by using transcriptomics and proteomics found that Protoanemonin significantly reduces gene expression and proteins secretion, which are known to be under the control by quorum sensing in Pseudomonas aeruginosa [14]. Moreover, they found genes activation and gene products involved in the iron deficiency reaction.…”
Section: Fig 3 Chelidonic Acidmentioning
confidence: 99%
“…The classical acyl‐homoserine lactone is present is some but no all of the P. putida strains and relatives, but ways to communicate via volatile fatty acids and other signals have been recently proposed (Fernández‐Piñar et al ., ). In this issue Bobadilla Fazzini and colleagues () show that two strains of Pseudomonas , B13 and reinekei MT1, use protoanemonin (Blasco et al ., ) as a quorum‐sensing signal, a role that has to be added to the already described role of being an antibiotic. This raises a very relevant point: what is an antibiotic and which is (are) their role in the natural environment?…”
Section: Comparing P Putida With Its Relativesmentioning
confidence: 99%